Identification of Potential MicroRNA-MRNA Regulatory Relationship Pairs in Irritable Bowel Syndrome with Diarrhea - Yan, Wenli; Kan, Zunqi; Li, Zhaofeng; Ma, Yuxia; Du, Dongqing (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Irritable bowel syndrome (IBS) is the most common gastrointestinal disease worldwide, with diarrhea-predominant irritable bowel syndrome (IBS-D) being the prevalent subtype. However, its pathogenesis remains unclear. Research has increasingly focused on identifying genetic factors in the mechanisms underlying IBS. Objective: We aimed to explore key gene nodes and potential microRNA-mRNA regulatory pairs of IBS-D using bioinformatics methods. Methods: We downloaded the GSE36701 microarray dataset from the Gene Expression Omnibus database and obtained 1358 differentially expressed mRNAs by analyzing mRNA profiles using the GEO2R analysis tool. Based on our previous study, we used TargetScan, miTarBase, and miRDB to predict the downstream genes of three known microRNAs (hsa-let-7b-5p, hsa-miR-19b-3p, and hsamiR- 20a-5p), and the microRNA-mRNA regulatory network was visualized using Cytoscape. Results: A total of 795 downstream target genes were found in TargetScan, miRTarBase, and miRDB databases, and 50 candidate genes were obtained. The Metascape and STRING databases were used to perform enrichment analysis and construct a protein-protein interaction network of candidate genes. Finally, we constructed a network of 3 microRNAs and 50 candidate mRNAs, among which 28 negative relation ship pairs and 5 key axes (hsa-miR-20a-5p/VEGFA, hsa-let-7b- 5p/MSN, hsa-let-7b-5p /PPP1R16B, hsa-19b-3p/ITGA2, and hsa-19b-3p/PIK3R3) were identified. Conclusion: We report five novel microRNA-mRNA regulatory axes in IBS-D pathogenesis and speculated that PIK3R3, negatively regulated by hsa-miR-19b-3p, may regulate NF-ΚB production through the PI3K/Akt pathway, which accounts for the occurrence of clinical symptoms in IBS-D patients. Our findings may offer key biomarkers for IBS-D diagnosis and treatment.
Keywords: IBS-D